KETERKAITAN BUDAYA ORGANISASI DAN KEDISIPLINAN GURU DALAM MEMPENGARUHI PRESTASI BELAJAR SANTRI - ANDI HASRYNINGSIH ASFAR; HERI IRAWAN (Jurnal Akademika, 2018)
The background of this research is the value of student achievement for class A, B and C in semesters 1 and 2, especially for class XII experiencing a fluctuating level. This study aims to determine the effect of organizational culture and discipline of teachers on student achievement in boarding school Al-MubarokSerang City. The independent variable is Organization Culture (X1) and Discipline (X2), for the dependent variable is Learning Achievement (Y). The research method used is quantitative method. The population in this study is all teachers in boarding school Al-MubarokSerang city as many as 73 teachers. Given the total population of 73 respondents, the authors took the decision to use the sampling technique that is non probabillity sampling using saturated sampling technique. Data analysis techniques used include classical assumptions, correlation, coefficient of determination, multiple linear regression analysis and hypothesis testing. The result of the research on the table of coefficiens obtained the result of regression analysis obtained t value 4,772 while t table 1,994 that tcount>ttable (4,772> 1,994) and significance value 0.000 <α (0,05) h0 rejected. While the Discipline of Learning Achievement obtained the results of regeresi analysis obtained t value 5,696 while t table 1.994 then tcount>ttable (5,696> 1,994) and significance value 0.000 <α (0,05) then H0 rejected. Conclusion of research based on the above calculation then there is a significant influence between the Organization Culture on Student Achievement of Santri and there is a significant influence between discipline on student learning achievement. Based on the analysis results can be concluded that simultaneously independent variables Organizational Culture and Discipline significantly influence the Achievement of Student Learning in Boarding School Al-MubarokSerang City.Keywords: Organizational Culture, Discipline and Learning Achievement